2001
DOI: 10.1046/j.1365-2036.2001.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin‐resistant Staphylococcus aureus infection of percutaneous endoscopic gastrostomy sites

Abstract: Background: Antibiotic prophylaxis for percutaneous endoscopic gastrostomy insertion remains controversial. The bacteriology of peristomal infection following percutaneous endoscopic gastrostomy insertion has been poorly studied, leading to uncertainty regarding the optimum choice of antibiotic for prophylaxis. Aim: To investigate the bacteriology of peristomal infection following percutaneous endoscopic gastrostomy insertion and to determine the contribution of methicillin‐resistant Staphylococcus aureus. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 14 publications
4
37
0
1
Order By: Relevance
“…Our results also showed that most of the bacteria isolated were flora found in the oral cavity. Consistent with the results of previous studies [13][14][15][16], MRSA was the major pathogen of PEG-site infections in our study. Thus, current guidelines that recommend antibiotic prophylaxis may be inappropriate for control of infection after PEG insertion [7,8].…”
Section: Discussionsupporting
confidence: 95%
“…Our results also showed that most of the bacteria isolated were flora found in the oral cavity. Consistent with the results of previous studies [13][14][15][16], MRSA was the major pathogen of PEG-site infections in our study. Thus, current guidelines that recommend antibiotic prophylaxis may be inappropriate for control of infection after PEG insertion [7,8].…”
Section: Discussionsupporting
confidence: 95%
“…More recent studies [7][8][9][10] have shown the emergence of methicillin-resistant Staphylococcus aureus (MRSA) as a major pathogen of PEG site infections and raised the question whether the currently recommended prophylactic antibiotics are appropriate [10]. There is also no agreement about the proper use of antibiotic prophylaxis prior to PEG placement in different patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011 The Infectious Diseases Society of America published the first guidelines for the treatment of MRSA infections in hospitals and ambulatory settings, which was an important step in the elaboration of new prophylactic and therapeutic protocols in health institutions (11) . A cephalosporin-based prophylaxis is usually suggested to decrease peristomal infection after PEG insertion (2,18) but these antibiotics are unlikely to be useful in the prevention of PEG-site infections caused by MRSA and resistant strains of Pseudomonas aeruginosa (9) . A recent paper in the British Medical Journal (BMJ) suggested the use of co-trimoxazol in the PEG prophylaxis (3) .…”
Section: Peristomal Infection After Percutaneous Endoscopic Gastrostomentioning
confidence: 99%